PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE QUESTIONS STUDENTS HAVE (QSH) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Yani, Evi; Anggraini, Villia; febriana, Rina (Pendidikan Matematika, 2014)
ABSTRACTÂ This research of background was the lackÂ  of students want to asked some questions and understanding mathematical concept still low, It can be seen at result of student mathematics at eight grade of SMPN 2 Lembah Melintang. This research purpose was to determined whether studentsâ understanding of mathematical concept by applied active learning strategy Questions Students Have type better at SMPN 2 Lembah Melintang. This was an experimental research and applied random research toward the subject. Population was students at eight grade of SMPN 2 Lembah Melintang. Technique of data colection was random, VIII4 as experimental class and VIII3 as control class. The instrumentation was final test and used essay form with reliability r11=0,84. Technique of data analyse used t âtest. Based on the data analised,Â  means of experimental was 74,81 higher than control 63,15. From the hypothesis testing got t-calculated 2,134 and t-table 1,664 because t-alculated higher than t-table so, research hypothesis was accepted. It concluded that understanding of mathematical concept by applied active learning strategy Questions Students Have type better than the understanding of mathematical concept by applied conventional learning at SMPN 2 Lembah Melintang at trust level 95%.